Human talent: General overview - Issurin, V. (EWF Scientific Magazine, 2018)
The presented data mostly relate to research where talent was studied with regards to various branches of human activities. It can be claimed that the majority of researchers and analysts draw the conclusion that hereditarily transmitted factors are decisive contributors for extraordinary abilities and excellence, which are qualified as talent. Importantly, convinced advocates of natural talent do not deny the necessity and importance of purposeful education, highly dedicated practice, and persistent training. On the other hand, the supporters of priority of environmental factors in human talent will not always admit to a contribution of inborn features in achievement of pure excellence in a given domain. These general positions and contrasting arguments definitely affect our understanding of the current situation in sport science and sport practice. However, a certain specificity, and even uniqueness, of sport reality give us a substantial privilege in the recognition and final identification of talent. Indeed, the inherent competitiveness of sport and availability of objective indicators of excellence provide analysts with the key for final qualification of the talented individual based on his/her achievements and records in world sport.